Smart Electrical Appliances Application for UTHM Pagoh Residential College - Zaidi, Ammar Muaz; Mohammad Kamal, Muhammad Akif Fahmi; Asmawi, Mohammad Danish Fitriey; Kassim@Kasim, Noordiana (Multidisciplinary Applied Research and Innovation, 2024)
Wasting electricity has become a habit. This is because of the irresponsible attitude of users when using electricity in the house and their laziness to turn of the fan and light switches when they are done using them. This project seeks to develop a Smart Electrical Appliance Application for UTHM Pagoh Residential College that blends Internet of Things (IoT) technology with real-world appliances such as lights and fans. This project will provide an alternative solution to the issue of inefficient and wasteful use of electricity by providing a convenient and efficient method for users to control their electrical appliances from a distance. The scope of this project is based on one room in the UTHM Pagoh residential college and is equipped with light bulbs and a fan with a DC motor that can be controlled using the smartphone application. This application was designed to reduce the cost of electricity and indirectly will assist college residents in managing their time properly. This project aims to tackle the inefficient electricity consumption caused by irresponsible residents that did not switch off their electrical appliances when leaving the room. It aims to encourage more efficient and convenient electricity usage through the use of IoT technology. C++ programming language has been used to connect the ESP8266 Wi-Fi module with the Blynk application to control the electrical appliances through smartphones while the voice control function with using Google Assistant also is applied for this project using the IFTT software. The interaction between user and Blynk application will send a signal to the Wi-Fi module that will interact with the relay module which will result in the switching ON or OFF of the electrical appliances. The project recognizes the benefits of IoT in enhancing various aspects of life, including energy conservation and reducing costs.